Autism Spectrum Disorders - Advances at the End of the Second Decade of the 21st Century 2019
DOI: 10.5772/intechopen.84790
|View full text |Cite
|
Sign up to set email alerts
|

Autism in the Classroom: Educational Issues across the Lifespan

Abstract: This chapter reviews educational strategies and legal policies impacting effective schooling for children, youth, and young adults. Emphasis is on the classroom manifestation of autism spectrum disorder (ASD), and how general education teachers can effectively facilitate learning. Within early school years, the importance of positive student-teacher relationships (STRs) in the face of challenging behaviors is discussed, including ways to build positive STRs. In middle and high school, social relationships serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 66 publications
0
16
0
1
Order By: Relevance
“…Later in childhood and during the early school years, the tendency for improvement is either reduced (Fountain et al, 2012), plateaus (Georgiades et al, 2021) or shifts to an increase in severity (Clark et al, 2017). The transition to school, which takes place at around age 6, presents children with new and complex challenges such as increasing social demands, needing to communicate and establish beneficial relationships with teachers and peers, and adjusting to an unknown environment and schedule (Bolourian et al, 2019; Nuske et al, 2019). Georgiades et al (2021) suggested that this major transition creates a “turning point” at around age 6 for many autistic children that can exacerbate their symptoms or halt improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Later in childhood and during the early school years, the tendency for improvement is either reduced (Fountain et al, 2012), plateaus (Georgiades et al, 2021) or shifts to an increase in severity (Clark et al, 2017). The transition to school, which takes place at around age 6, presents children with new and complex challenges such as increasing social demands, needing to communicate and establish beneficial relationships with teachers and peers, and adjusting to an unknown environment and schedule (Bolourian et al, 2019; Nuske et al, 2019). Georgiades et al (2021) suggested that this major transition creates a “turning point” at around age 6 for many autistic children that can exacerbate their symptoms or halt improvement.…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of how autism affects learning is a critical step to overcome these challenges. There are limited studies into how best to assist the support faculty in accommodating students with ASD in their classrooms [17]. Therefore, this paper aims to examine how therapeutic intervention can improve learning, especially for ASD children.…”
Section: Challenges Autistic Children Face In Learningmentioning
confidence: 99%
“…Moky klos komandos bendradarbiavimas su tėvais, jų kaip lygiaverčių partnerių pri pažinimas yra vienas iš pagrindinių tėvų pasitenkinimo mokykla, jų įtraukties į vaiko ugdymo procesą kriterijų (Chaidi ir Drigas, 2020). Tėvai yra savo vaiko ekspertai ir gali suteikti informacijos, kuri bus vertinga ugdant ASS turintį vaiką (Bolourian, Stavropoulos, Blacher, 2019). Tėvų įžvalgos, dalijimasis patirtimi, bendradarbiavimas sprendžiant kylančius sunkumus pripažįstamas kaip svar bus veiksnys kuriant įtraukiąją ugdymo aplinką mokykloje.…”
Section: Diskusijaunclassified